Determinan Current Asset Terhadap Pertumbuhan Laba - Septyaningrum Septyanigrum; Anita Wijayanti; Rosa Nikmatul Fajri (Journal of Economics Development Issues, 2020)
Profit is often used as a benchmark in achieving the performance results of a company in a certain period, where profit is an indicator to determine the state of the economy or company performance. With the financial ratios said to have uses if it can be used to predict economic phenomena that occur. One of them is profit change. The purpose of this research was to analyze Cash Turnover, Receivable Turnover, and Inventory Turnover on Profit Growth. The population in this research is LQ45 companies listed on the Indonesia Stock Exchange in 2017-2018 using purposive sampling techniques. The number of samples taken in this research were 15 companies using multiple linear analysis. The results showed that Accounts Receivable Turnover had an effect on Profit Growth, while Cash Turnover and Inventory Turnover had no effect on Profit Growth. The benefits of research to help investors support the decision making process, in addition to seeing the company's performance in generating profits.